Numerical Simulation of Sediment Transport and Morphological Change of Upstream and Downstream Reach of Chi-Chi Weir - Yeh, Keh-Chia; Wang, Sam S.Y.; Chen, Hungkwai; Liao, Chung-Ta; Jia, Yafei; Zhang, Yaoxin (IntechOpen, 2010)
None